Uresničevanje dvojezičnega izobraževanja gluhih otrok v slovenskem šolskem sistemu - Pavlič, Matic (Slavia Centralis, 2020)
Advances in Bilingual Education for Deaf Children in Slovenia Deaf children may receive different types of education that differ with respect to the language used in class and the degree of inclusion in ordinary school system. In Slovenian schools, the deaf children are not necessarily provided with an input of a fully perceivable language while the professionals do not receive enough updated information about the advances in bilingual and bimodal education of the deaf. This article aims to fill these two gaps and put forth the arguments for above mentioned approach.